A single-centre randomised controlled trial comparing the standard method and target-controlled infusion as a method of administering cefoxitin, which is used to prevent surgical site infections in colorectal surgical patients: study protocol - Ha-Jung Kim; Kyung Mi Kim; Jong Lyul Lee; In Ja Park; Byung-Moon Choi (Trials)
Abstract Background Prophylactic parenteral administration of antibiotics is strongly recommended to prevent surgical site infection (SSI). Cefoxitin is mainly administered intravenously in colorectal surgery. The current standard method for administering prophylactic antibiotics in adults is to administer a fixed dose quickly before skin incision. The percentage of time that the unbound concentration is maintained above the minimum inhibitory concentration (fT > MIC) during surgery is used as a surrogate measure for the effectiveness of prophylactic antibiotics. Target-controlled infusion (TCI) is a method of administration that changes the infusion rate to maintain a constant target concentration set by the user in consideration of the patient’s physical characteristics. When cefoxitin is administered using the TCI method, it is possible that fT > MIC can be well maintained while reflecting the patient’s physical characteristics compared to the standard method. Methods This prospective, single-centre, parallel-arm, single-blinded, randomised controlled trial with a 1:1 allocation was designed to compare the effectiveness of the TCI method with that of the standard cefoxitin administration method. We shall enrol 2494 patients scheduled to undergo colon or rectal surgery. Prior to the procedure, we shall randomise each patient to the control group (standard administration method) or study group (TCI method). In the control group, 2 g of cefoxitin was dissolved in 100 ml of normal saline and administered for approximately 10 min. Redosing was performed every 2 h from the start of the first dose of cefoxitin. In the study group, 2 g of cefoxitin was dissolved in 50 ml of normal saline and administered using a commercialised TCI syringe pump until the end of surgery. It was administered at a target concentration of 80 μg/ml using the total concentration pharmacokinetic model of cefoxitin. In all groups, 2 g of cefoxitin was administered using the standard administration method 12 h after the end of surgery. The primary outcome will be the incidence of SSI. The secondary outcome will be the administered dose of cefoxitin. Preoperative, intraoperative, and postoperative data were collected. Discussion This study will provide evidence for the effectiveness of administering cefoxitin using the TCI method compared to the standard method. Trial registration ClinicalTrials.gov, NCT05253339 , Registered on February 23, 2022 {2a, 2b}.